Антарктические микроорганизмы, устойчивые к высоким концентрациям Hg2+, Cu2+, Cd2+ и СrО2− - Таширев, А.Б.; Романовская, В.А.; Сиома, И.Б.; Усенко, В.П.; Таширева, А.А.; Матвеева, Н.А.; Рокитко, П.В.; Копытов, Ю.П.; Серединин, Е.С.; Мизин, Д.А.; Подгорский, В.С. (Видавничий дім "Академперіодика" НАН України, 2008)
The microbiological analysis of various biotopes which have been selected on the islands Galindez, Skua, Barchans, Irizar, Uruguay, Jalour, Petermann, Berthelot, Cruls, and King-Georg located in the western Antarctic Region and at the western coast of the Antarctic peninsula, cape Rasmussen and cape Tuxen, was carried out. In the majority of ground biotopes (the soil, mosses, lichens, lake silt, water, humus) of the investigated Antarctic Region, the microorganisms resistant to heavy metals (100. . . 500 ppm of ions Сr, Cu, Cd, or Hg) are revealed. Thus, for the first time, the wide occurrence of microorganisms resistant to a bactericidal concentration of heavy metals in the Antarctic Region is shown. Uniqueness of a phenomenon consists in a combination: (1) ability of microorganisms to grow at superhigh concentration of heavy metals, (2) it is non-comparable by low concentration of heavy metals in the Antarctic samples (from 0.02 up to 40 ppm), (3) presence of metal-resistant microorganisms in all ground biotopes of the Antarctic Region, (4) high number of metal-resistant microorganisms in these biotopes (104 . . .105 cells/g of a substrate).